OC-076 Endoscopic Placement of Fully Covered Self Expanding Metal Stents (FC-SEMS) into the Pancreatic Duct of Patients With Painful Chronic Pancreatitis. (17th August 2016) - Wadsworth, CA; Sangwaiya, A; Rajaratnam, R; Butt, MA; Phillips, N; Bansi, D; Vlavianos, P; Westaby, D
Abstract : Introduction: Endoscopic placement of plastic stents into the pancreatic duct (PD) has achieved disappointing outcomes in the treatment of painful chronic pancreatitis (CP), when compared to surgery. However, pancreatic bypass surgery or resection is associated with significant morbidity. Recently, FC-SEMS have proven more effective than plastic stents in the management of strictures of the bile duct. We aimed to assess feasibility, safety and efficacity of PD FC-SEMS in the management of painful CP. Methods: Patients were recruited at a single tertiary UK pancreatobiliary centre. Patients were considered for PD FC-SEMS after demonstration of i) CT/MR imaging criteria of chronic pancreatitis including dilatation of the main PD and ii) characteristic pancreatic pain resistant to analgesia. Patients' treatment plans were all determined in a MDT meeting. All patients gave informed consent. Visual analogue pain scores and analgesia requirements were documented prior to intervention and at each follow up appointment. At ERCP, PD cannulation was attempted from the major papilla in all cases. In cases of pancreas divisum, or where PD cannulation via the major papilla failed, cannulation of the minor papilla was attempted. On cannulation of the PD, a pancreatic sphincterotomy was performed before deployment of a 60 mm by 8 mm FC-SEMS. Stent removal was scheduled between 10 and 14 weeks after placement. Results: 35 patients (22 M) had FC-SEMS placed into the PD. The median age at time of stent placement was 55 y (range 21–71). In 24 cases the stent was placed via the major papilla, 11 were placed via the minor papilla. The median interval between stent placement and removal was 86 days (13–252) with median follow up of 22 months (3–33). One patient developed a Santorini duct abscess, which precipitated early stent removal but was otherwise managed conservatively. One instance of retrograde stent migration was noted and was managed endoscopically. 20 (57%) patients reported a complete resolution of pancreatic pain, 10 (29%) a partial response and 5 (14%) no response. A concomitant cessation or decline in the use of opiate analgesia was demonstrated. Of the five non- responders, three proceeded to lateral pancreatojejunostomy – two of whom reported a full symptomatic response. Conclusion: Placement of FC-SEMS into the pancreatic duct of patients with painful chronic pancreatitis appears to be feasible and safe and does not preclude subsequent surgical intervention. The lengthy follow up data presented suggests that this endoscopic approach may be more effective than would be expected from historical studies of the use of plastic pancreatic duct stents. A controlled trial is warranted. Disclosure of Interest: None Declared